Faktor yang Mempengaruhi Perilaku Ibu dalam Pencegahan Pertusis pada Anak Usia ≤ 6 Tahun di Kecamatan Ingin Jaya Aceh Besar - Naila Sabila; Farrah Fahdhienie; Putri Ariscasari (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Pertussis is a respiratory infection that can be prevented through immunization and a clean and healthy lifestyle. However, pertussis cases are still found due to low public awareness in prevention. This study aims to identify factors that influence pertussis prevention behaviors among mothers in Reuloh and Dham Ceukok villages, Aceh Besar Regency. The study used a quantitative approach with a cross-sectional design. The sample was taken by simple random sampling from mothers who have children aged ≤6 years, with data collected through questionnaires in January 2025 and analyzed using logistic regression in the STATA program. The results of univariate analysis showed that most respondents had good pertussis prevention behavior (52.2%), good personal hygiene (54.1%), and complete child immunization status (60.8%). Multivariate analysis showed that personal hygiene (OR = 3.772; p = 0.015) and child immunization status (OR = 0.321; p = 0.002) had a significant effect on pertussis prevention behavior. It was concluded that maternal personal hygiene and child immunization status are important factors in pertussis prevention. Education and improved access to immunization services need to be strengthened, especially in remote areas.